Pengembangan Modul Mata Kuliah Berbicara Berbasis Metode Jigsaw - Maulidia Tifani Alfin Nur Hardiana; Siti Aisah (Jurnal Pendidikan Edutama, 2021)
Abstract: This study aims to describe the initial trials of the speaking practice module using the jigsaw method for the Speaking and Learning course. This is a type of research and development (R&D) using the Borg & Gall development model which consist of several steps (1) analysis of need; (2) planning; (3) development of product; (4) validation and revision of product; and (5) trial of product. The trial of product was conducted on 12 students. The data was collected by using a product trials questionnaire to get student responses after using the speaking practice module that had been developed. The following are the results of research: (1) the availability of a speaking practice module that has been developed is able to facilitate and motivate students to practice speaking. (2) The product of the development of this speaking practice module consists of public speaking material, this jigsaw method is very helpful for students in understanding a type of speaking and explaining it to their friends in their group. (3) This product has met the product eligibility criteria shown from the results of the student response questionnaire with details on the presentation aspect with the "good" category with a score of 4.00, the material aspect with the "very good" category with a score of 4,3, and the aspect of benefits with a "good" category with a score of 4.00. The results of the validation of the speaking practice module using the jigsaw method are very helpful for students in speaking practice.  Keywords: module development, speaking subject, jigsaw method. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan hasil uji coba awal modul praktik berbicara dengan metode jigsaw untuk mata kuliah Berbicara dan Pembelajarannya. Ini merupakan jenis penelitian dan pengembangan (R&D) dengan menggunakan model pengembangan Borg & Gall yang terdiri atas beberapa langkah, yaitu (1) analisis kebutuhan; (2) perencanaan; (3) pengembangan produk; (4) validasi dan revisi produk; dan (5) uji coba produk. Uji coba dilaksanakan pada 12 mahasiswa. Pengumpulan data dilakukan dengan angket uji coba produk untuk mendapatkan tanggapan mahasiswa setelah menggunakan modul praktik berbicara yang telah dikembangkan. Berikut hasil penelitiannya: (1) ketersediaan modul praktik berbicara yang telah dikembangka mampu memfasilitasi dan memotivasi mahasiswa untuk melakukan praktik berbicara. (2) Produk pengembangan modul praktik berbicara ini terdiri atas materi berbicara di depan umum, metode jigsaw ini sangat membantu mahasiswa dalam memahami suatu jenis berbicara dan menjelaskannya kepada teman-teman di kelompoknya. (3) Produk ini telah memenuhi kriteria kelayakan produk yang ditunjukkan dari hasil angket tanggapan mahasiswa dengan rincian pada aspek penyajian dengan kualifikasi “layak” dengan skor 4,00, aspek materi dengan kualifikasi “sangat layak” dengan skor 4,3, dan aspek manfaat dengan kualifikasi “layak” dengan skor 4,00. Hasil validasi modul praktik berbicara dengan metode jigsaw sangat membantu mahasiswa dalam praktik berbicara.  Kata Kunci: pengembangan modul, mata kuliah berbicara, metode jigsaw.